The Cost-of-Living Index and Wage Determination - Martin, Jean-Marie (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 1949)
To what extent can the cost of living index be used in the negotiation of wage agreements ?